Determinants of low APGAR score among preeclamptic deliveries in Cipto Mangunkusumo Hospital: a retrospective cohort study in 2014 (Faculty of Medicine Universitas Indonesia, 2015)
Background: Preeclampsia has great implication on adverse neonatal outcome. Appearance, pulse, grimace, activity, respiration (APGAR) score at 1 or 5 minutes is one of the indicators of physiologic maturity of the infant. Therefore, the aim of this study was to know the correlation of APGAR score in preeclamptic deliveries with its risk factors. Methods: This study was a retrospective cohort. Data were collected from January to December 2013 including all preeclamptic women with singleton live pregnancies who delivered their babies in Cipto Mangunkusumo Hospital, Jakarta. The primary outcome was APGAR score. There were some determinants conducted in this study. Binary logistic was used as multivariate analysis to analyze the correlation between APGAR score and risk factors of preeclampsia, data were analyzed using chi square test. Results: Out of 450 preeclamptic women, 446 of them met the inclusion criteria. Low APGAR scores at 1 and 5 minutes were found in 19% (86/446) and 5.4% (24/446) of neonates respectively. Early onset of preeclampsia (adjusted OR = 4.577; 95% CI = 2.147 - 9.757), white blood cell ≥ 15,000/μL (adjusted OR = 3.315; 95% CI = 1.738 - 6.324), HELLP syndrome (adjusted OR = 2.00; 95% CI = 1.38 - 2.91) were independent risk factors for having infant with low APGAR score at 1 minute. Meanwhile, there was no significant risk factors at 5 minutes APGAR score after adjustment. Conclusion: Leukocytosis, early onset preeclampsia, preterm birth, and thrombocytopenia, severity of preeclampsia, and HELLP syndrome are independent risks of having infant born with low APGAR score at 1 minute in preeclamptic deliveries.